Expression of Monoamine Transporters, Nitric Oxide Synthase 3, and Neurotrophin Genes in Antidepressant-Stimulated Astrocytes - Kittel-Schneider, Sarah; Kenis, Gunter; Schek, Julia; van den Hove, Daniel; Prickaerts, Jos; Lesch, Klaus Peter; Steinbusch, Harry; Reif, Andreas (Frontiers in Psychiatry, 2012)
Background: There is increasing evidence that glial cells play a role in the pathomechanisms of mood disorders and the mode of action of antidepressant drugs. Methods: To examine whether there is a direct effect on the expression of different genes encoding proteins that have been implicated in the pathophysiology of affective disorders, primary astrocyte cell cultures from rats were treated with two different antidepressant drugs, imipramine and escitalopram, and the mRNA expression of brain derived neurotrophic factor (Bdnf), serotonin transporter (5Htt), dopamine transporter (Dat) and endothelial nitric oxide synthase (Nos3) was examined. Results: Stimulation of astroglial cell culture with imipramine, a tricyclic antidepressant, lead to a significant increase of the Bdnf mRNA level whereas treatment with escitalopram did not. In contrast, 5Htt was not differentially expressed after antidepressant treatment. Finally, neither Dat nor Nos3 mRNA expression was detected in cultured astrocytes. Conclusions: These data provide further evidence for a role of astroglial cells in the molecular mechanisms of action of antidepressants.